The ApoB/ApoA-1 ratio, the carotid intima-media THICKNESS AND its possible relationship - Yanela Yordanka Ortega Torres; Juan Valiente Mustelier; Luis Roberto Llerena Rojas; Nurys B. Armas Rojas; Ramón Suárez Medina; Yamilé Marcos Gutiérrez (ECIMED, 2015)
The ApoB/ApoA-1 ratio and the carotid intima media thickness are markers of atherosclerosis and cardiovascular risk. Objective: To determinate the ApoB/ApoA-1 ratio, the carotid intima media thickness and its possible relationship in the health area "Héroes del Moncada" population 2011-2013. Method: Descriptive transversal and observational study. Sample amount: 1004 individuals frame 40-70 years: Sample: 146 persons. Variables: ApoB/ApoA-1, carotid intima media thickness, age, sex, smoking, hypertension, obesity, triglycerides. Statistical analysis: As summary measures for qualitative variables there were used absolute frequencies, percent, and for the quantitative there used mean, standard deviations, standard errors, median, quartiles 1 and 3. It was also used a mean comparison: WILCOXON y KRUSKAL WALLIS. It was done a multiple lineal regression. There were adjusted the models of logistic regression. It was established a level of significance of 95%, p< 0.05.Results: The median of the ApoB/ApoA-1 ratio were bigger in men and they were higher depending on higher ages. The median of the carotid intima media thickness were bigger in men and they were higher depending on higher ages. As age goes up and the ApoB/ApoA-1 ratio, the carotid intima media thickness goes up too. Conclusions: The relationship among these cardiovascular risk markers was significant.